The Knowledge Level of Temporomandibular Disorders Pathophysiology by Dental Practitioners in Jakarta, Indonesia - Christopher Ryan Aliwarga; Carolina Marpaung (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: Temporomandibular disorder (TMD) is a common term used to describe the problems related to masticatory muscles, joints, and supporting tissues. TMD commonly causes orofacial pain and has been the subject of considerable research in the field of dentistry. The treatment chosen for patients who have TMD is largely determined by the knowledge of general dental practitioners. Objectives: The purpose of this research was to assess the understanding of TMD pathophysiology by such practitioners. Methods: Questionnaires were distributed randomly to general dental practitioners in private offices and hospitals in the area of Jakarta, Indonesia. The answers on the returned questionnaires were compared to those of TMD experts. Results: Of the 117 questionnaires distributed to general dentists, 105 were returned (89.7% response rate). The results showed an overall level of knowledge of TMD pathophysiology of 25%. Conclusion: The majority of general dental practitioners in Jakarta lack knowledge of TMD pathophysiology